Ex vivo evaluation of novel core tenorrhaphy patterns in dogs. Issue 6 (6th July 2021) - Chiu, King Wa; Duffy, Daniel J.; Chang, Yi‐Jen; Gaffney, Lewis; Fisher, Matthew B.
Abstract: Objective: To compare the biomechanical properties and gapping characteristics of four novel tenorrhaphy patterns in a canine flexor tendon model. Study Design: Ex vivo, randomized, biomechanical study. Sample Population: Superficial digital flexor tendons of 60 forelimbs (30 dogs). Methods: Each tendon was transected 25 mm distal to its musculotendinous junction prior to tenorrhaphy with 2‐0 polypropylene. Repair patterns included the three‐loop pulley (3LP, control), exposed double‐cross‐lock (ExDCrL), embedded double‐cross‐lock (EmDCrL), triple‐circle‐lock (TCiL), and Modified‐Tang patterns (MTang) were randomly assigned to each experimental group ( n  = 12/group). Yield, peak, and failure loads, gap formation and failure modes were compared. Results: Tendons repaired with ExDCrL ( p  < .0001), EmDCrL ( p  < .0001), and MTang ( p  < .0001) sustained yield, peak, and failure loads ~2.2x, ~2.0x, and ~1.9x, respectively, greater than those repaired with 3LP. Loads to 1 and 3 mm gapping were also higher for ExDCrL ( p  < .0001), EmDCrL ( p  < .0004), and MTang constructs ( p  < .0017) compared to 3LP. Although TCiL constructs sustained higher loads, their resistance to gap formation did not differ from that of 3LP repairs. Failure mode differed between groups ( p  < .0001), EmDCrL, ExDCrL, MTang, and TCiL constructs failing predominantly by suture breakage compared to 3LP repairs that failed by suture pull‐through. Conclusion: Use of novel patterns ExDCrL, EmDCrL, and MTang improved resistance to loads and gap formation and were biomechanically superior compared to 3LP in healthy canine tendon repairs. Clinical Significance: These results justify in vivo evaluation of ExDCrL, EmDCrL, or MTang pattern for tenorrhaphy in dogs.